PENGARUH PROFITABILITAS, LIKUIDITAS, UKURAN PERUSAHAAN, STRUKTUR AKTIVA, DAN RISIKO BISNIS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2018-2021 - Silalahi, Donalson; Limbong, Sriladepa; Munthe, Kornel; Sipahutar, Robinson; Purba, Saut (Jurnal Manajemen dan Bisnis, 2023)
The purpose of this research was to determine and explain the influence of the profitability, liquidity, firm size, asset structure, and business risk on the capital structure of manufacturing companies listed on the Indonesian Stock Exchange for the 2018-2021 period. This research focuses on food and beverage sub-sector manufacturing companies and obtain 30 companies as sample. The data analysis technicque used multiple regression model. The results show that the profitability and liquidity have a negative and significant effect on capital structure. Firm size and asset structure have a negative and insignificant effect on capital structure, and business risk have a positive and insignificant effect on capital structure. Simultaneously that profitability, liquidity, firm size, asset structure, and business risk are able to explain variations in the capital structure of manufacturing companies listed on the Indonesian Stock Exchange for the 2018-2021 period by 46,4 percent.